The impact of computer display performance on the quality of digital radiographs: a review. - Butt, Alison; Mahoney, M; Savage, N W (Australian Dental Journal, 2012)
Radiography makes an essential contribution to the processes of examination, diagnosis and treatment planning in dentistry. While the use of film-based imaging still predominates in dentistry, digital imaging is gaining wider acceptance and the use of this modality is anticipated to expand in the future. Two concerns associated with this transition have been raised in the literature. The first of these is the dissatisfaction experienced by many dental professionals with quality of digital radiographs when compared to plain film. In addition, there are indications that practitioners feel limited in their understanding of those factors impacting on digital image quality. One key area highlighted in the literature as having a significant influence on digital radiographic quality and interpretation concerns the performance of the display device. Within the last decade, research derived from the fields of medical radiology and physics have demonstrated that suboptimally performing displays degrade image quality, thereby increasing the potential for compromised diagnostic outcomes. In the field of medicine, this has resulted in the establishment of standards applicable to computer displays used in diagnostic radiology. Conversely, limited guidelines exist in the field of dentistry. The aim of this review is to provide an outline of these standards and highlight the important relationship between computer display performance and digital image quality.